High resolution X-ray spectroscopy of V4641 Sgr during its 2020 outburst. Issue 1 (6th August 2022) - Shaw, A W; Miller, J M; Grinberg, V; Buisson, D J K; Heinke, C O; Plotkin, R M; Tomsick, J A; Bahramian, A; Gandhi, P; Sivakoff, G R
ABSTRACT: We observed the Galactic black hole X-ray binary V4641 Sgr with the high resolution transmission gratings on Chandra during the source's 2020 outburst. Over two epochs of Chandra gratings observations, we see numerous highly ionized metal lines, superimposed on a hot, disc-dominated X-ray continuum. The measured inner disc temperatures and luminosities imply an unfeasibly small inner disc radius, such that we suggest that the central engine of V4641 Sgr is obscured, and we are viewing scattered X-rays. We find that the emission lines in the Chandra spectra cannot be constrained by a single photoionized model, instead finding that two separate photoionized model components are required, one to reproduce the iron lines and a second for the other metals. We compare the observed X-ray spectra of V4641 Sgr to optical studies during previous outbursts of the source, suggesting that the lines originate in an accretion disc wind, potentially with a spherical geometry.